6=6v+6(v-7)

Simple and best practice solution for 6=6v+6(v-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=6v+6(v-7) equation:


Simplifying
6 = 6v + 6(v + -7)

Reorder the terms:
6 = 6v + 6(-7 + v)
6 = 6v + (-7 * 6 + v * 6)
6 = 6v + (-42 + 6v)

Reorder the terms:
6 = -42 + 6v + 6v

Combine like terms: 6v + 6v = 12v
6 = -42 + 12v

Solving
6 = -42 + 12v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-12v' to each side of the equation.
6 + -12v = -42 + 12v + -12v

Combine like terms: 12v + -12v = 0
6 + -12v = -42 + 0
6 + -12v = -42

Add '-6' to each side of the equation.
6 + -6 + -12v = -42 + -6

Combine like terms: 6 + -6 = 0
0 + -12v = -42 + -6
-12v = -42 + -6

Combine like terms: -42 + -6 = -48
-12v = -48

Divide each side by '-12'.
v = 4

Simplifying
v = 4

See similar equations:

| 4-3x-1=3x+15 | | -2/5*3/2 | | 1920*x=14 | | 2x+4+58=180 | | 1.2x=14+X | | x^2+x-34=6x+2 | | 1080*x=915 | | 1080-x=165 | | x^2-14x+21=-4x-3 | | -6(4-3x)-7=-2(2-3x) | | 6x-42=10x+40 | | 2(s+2)=8 | | x^2+6x+14=6 | | p/10=7 | | (6a-5)(3a+1)=0 | | 14(4m+11)= | | -5(x-3)+2(a-9)= | | forX^2=324 | | 2x^2+12x+36x=0 | | -5(x-31)=115 | | (2a^2b^4+3ab)+(5ab-2a^2b^4)= | | 10x+11=8x+15 | | 10b-2x=16 | | (-4)x(9)-(5)x(-2)= | | 5[x+3]=2[3x+12] | | 2y=2x-1 | | 2n^2+13n-5=2 | | 3x(x)+x-4=0 | | x^2/X^0.5 | | -6(-3-2-5)= | | 208-w=40 | | 7x-1=x+10 |

Equations solver categories